Corporate tax planning and enforcement - Daniel Dyck (Arbeitskreis Quantitative Steuerlehre (arqus), 2025)
This study investigates how strategic interactions between corporate tax planning and tax enforcement are affected by two policy instruments: strengthening tax enforcement by increasing the number of specialized enforcement staff and improving tax audit technologies. I employ an economic model with a board of director's investment in a Tax Control Framework (TCF) and a tax manager's tax planning effort jointly shaping corporate tax planning and a tax auditor's technology-based audit decision. I show that the board only invests in the TCF when the enforcement environment is sufficiently strict, because it trades-off the costs and benefits of tax planning. Since strengthening tax enforcement decreases tax planning effort, the result can be less investment in a TCF in a strict enforcement environment, implying that TCF investment and enforcement can be strategic substitutes. Strikingly, I identify conditions under which improvements in tax audit technology increase corporate tax planning and impair tax audit efficiency, due to a crowding out of audit incentives. This result contradicts the view that improving audit technologies is universally effective, particularly in tax authorities with adequate staffing.
Keywords: H26; H32; M42; M48; C70; 330; tax control framework; tax planning; tax risk management; tax audit technology; tax enforcement